Communication: UV photoionization of cytosine catalyzed by Ag+ - Taccone, Martín Ignacio (2015)
The photo-induced damages of DNA in interaction with metal cations, which are found in various environments, still remain to be characterized. In this paper, we show how the complexation of a DNA base (cytosine (Cyt)) with a metal cation (Ag+) changes its electronic properties. By means of UV photofragment spectroscopy of cold ions, it was found that the photoexcitation of the CytAg+ complex at low energy (315-282) nm efficiently leads to ionized cytosine (Cyt+) as the single product. This occurs through a charge transfer state in which an electron from the p orbital of Cyt is promoted to Ag+, as confirmed by ab initio calculations at the TD-DFT/B3LYP and RI-ADC(2) theory level using the SV(P) basis set. The low ionization energy of Cyt in the presence of Ag+ could have important implications as point mutation of DNA upon sunlight exposition.